The World Trade Organization's Records and Archives Management Policy: an overarching framework for ensuring information continuity. Issue 2 (1st August 2021) - Galán, Jesús; Bressi, Maria
Abstract : This article describes the process of creation and discussion of the World Trade Organization (WTO) Records and Archives Management Policy, the first such policy ever issued by the Secretariat, after 25 years of existence. It outlines, firstly, the methodology followed to assemble and articulate the Policy, and its alignment with the standards and best practice followed by other international organizations; secondly, how the Policy was presented to different stakeholders and approved; and thirdly, the structure and contents of the Policy which aims to be a comprehensive, cross-organizational records and archives management strategy to ensure accountability and transparency at all levels of the WTO. The lack of a regulatory framework and the specificity of Intergovernmental Organizations' (IGO) institutional structures can represent a challenge for archivists and records managers with regard to the creation and control of informational assets in a systematic and verifiable manner; the article suggests a methodology for the drafting and implementation of records and archives management principles in the context of such international organizations.